TREN DAN PETA TEMATIK INOVASI ILMU PENGETAHUAN DAN TEKNOLOGI DALAM OLAHRAGA PARALAYANG: ANALISIS BIBLIOMETRIK PUBLIKASI SCOPUS TAHUN 1989–2025 - Indardi, Nanang; Sumartiningsih, Sri; Hadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
Paragliding is an extreme air sport that requires the support of scientific and technological (S&T) innovation to ensure athlete safety and performance. However, comprehensive studies on trends and directions of research development in this field are still limited. This study aims to map trends and thematic maps of IPTEK innovation in paragliding based on Scopus-indexed publications for the period 1989–2025. The method used is quantitative descriptive with bibliometric analysis. Data were obtained through Boolean searches in Scopus and analyzed using VOSViewer to visualize the relationship between keywords. The results show a significant increase in publications in the last two decades. The findings indicate a significant increase in parameters with Cohen's d = 1.2, indicating a significant influence on the analyzed aspects, especially with advances in digital technology, biomechanical sensors, and data-driven safety systems. The most productive contributors come from Europe, particularly Germany, Switzerland, and the United Kingdom, with a predominance in aviation medicine. Thematic analysis reveals five main clusters: safety and injury risk, body physiology, participant participation and experience, paragliding activity trends, and aviation technology innovation. This study concludes that there has been a shift in research focus from medical aspects to the practical application of science and technology to improve safety, performance, and experience in paragliding, while also opening up opportunities for future interdisciplinary research development.